2019
DOI: 10.1111/are.14071
|View full text |Cite
|
Sign up to set email alerts
|

Hatching rate of Chinese sucker ( Myxocyprinus asiaticus Bleeker) eggs exposed to total dissolved gas (TDG) supersaturation and the tolerance of juveniles to the interaction of TDG supersaturation and suspended sediment

Abstract: Flood discharge containing excessive suspended sediments (SS) can result in total dissolved gas (TDG) supersaturation downstream of dams. It has been confirmed that high TDG levels and excessive SS cause serious threats to fish survival. To explore the effects of TDG supersaturation on the hatchability of Chinese sucker (Myxocyprinus asiaticus Bleeker) eggs, eggs were exposed to 100%, 125%, 130% and 135% TDG supersaturated water. The results showed that the hatching rates were 78.25%, 75.35%, 71.30% and 67.50%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 36 publications
1
13
0
1
Order By: Relevance
“…Previous studies have demonstrated that GBD symptoms are often found in fish exposed to TDG-supersaturated water [28][29][30][31]. Some typical GBD symptoms were described, such as excessive bubbles on the fins, exophthalmia, haemorrhages and swelling of the swimming bladder [6,22,32,33]. In this study, juvenile grass carp subjected to TDG-supersaturated water exhibited caudal fin bleeding, dorsal fin bubbles, loss of scales and abdominal swelling.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Previous studies have demonstrated that GBD symptoms are often found in fish exposed to TDG-supersaturated water [28][29][30][31]. Some typical GBD symptoms were described, such as excessive bubbles on the fins, exophthalmia, haemorrhages and swelling of the swimming bladder [6,22,32,33]. In this study, juvenile grass carp subjected to TDG-supersaturated water exhibited caudal fin bleeding, dorsal fin bubbles, loss of scales and abdominal swelling.…”
Section: Discussionsupporting
confidence: 49%
“…Ji et al [42] reported that Prenant's schizothoracin had higher mortality at high TDG levels (130% and 135%) than at low TDG levels (110% and 115%). Some researchers found that the tolerance of Chinese sucker decreased with increasing TDG levels [22,43]. In this study, the LT 50 values of large and small juvenile grass carp at the 130% TDG level (36.55 and 88.13 h, respectively) were much higher than those at the 140% TDG level (6.37 and 35.88 h, respectively) ( Table 1).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…In China, previous studies have shown that different benthic endemic species in the Yangtze River have diverse tolerance to TDG. According to Li et al, (2019), the LT 50 (50% survival probability) values of the Chinese sucker were 6.1, 4.5 and 3.1 h at 130, 135, and 140% TDG, respectively. In addition, Wang et al, (2015) [39] indicated that Prenant's schizothoracin in TDG supersaturated water at levels of 130, 135, and 140% possessed LT 50 values of 8.7, 8.0 and 4.6 h, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…TDG supersaturated water was generated by a system that is described in detail by Li et al, (2019) [27]. In the system, a compressor produced compressed air, which was injected into an autoclave in addition to the water from the water flume to create high TDG supersaturated water.…”
Section: Experimental Devicesmentioning
confidence: 99%